Na alfabetização: o que dizem as crianças negras sobre a negritude - Lopes Filho, Agenor (My University, 2025)
The writing entitled In literacy: what black children say about blackness reports meetings that happen through five workshops on blackness, with black children in literacy, enrolled in state schools in the city of Bento Gonçalves, a municipality in the mountain chains of Rio Grande do Sul. It brings the following research problem in discussion: What do black children enrolled in the second year of literacy in state schools in the city of Bento Gonçalves - RS say about blackness? In presenting the writing of this dissertation topic, the act of a black father is driven by the demonstration of racism caused at school, directly to his son Arthur and, with the movement of the research, he claims, through writing, the place of a research method as a black cartographer and its expression through drawings and the writing of the dissertation, which only happens with black authors, which already occurs due to this political-scientific positioning of a research practice for blackness. Along with the method, conceptual combats occur over the racialization of black people, from a perspective of blackness. The general aim of this research process is to map what black children enrolled in the second year of literacy in state schools in the city of Bento Gonçalves - RS say about blackness and, based on this, we have the following investigative topics: I. Expressing, through a cartography of drawings, the operators in the production of blackness; II. Mapping the presence of black children in the first year of literacy, using self-declared race data provided by those responsible, in state schools in the municipality of Bento Gonçalves - RS; III. Elaborate the black workshop, so that the black children listed in the mapping of objective II can express their blackness; IV. Point out what the black children say when they participate in the black workshop. Ten children from the second year of literacy, from five schools in the municipality, took part in the ateliers-negritude and this space shows the record of what the children say about racism, territorialized in their curly hair. [resumo fornecido pelo autor]
A escrita intitulada Na alfabetização: o que dizem as crianças negras sobre a negritude narra encontros que acontecem por meio de cinco ateliês-negritude, com crianças negras na alfabetização, matriculadas nas escolas estaduais da cidade de Bento Gonçalves, município da região serrana do Rio Grande do Sul. Traz como tensionamento o seguinte problema de pesquisa: o que dizem as crianças negras matriculadas no segundo ano da alfabetização nas escolas estaduais da cidade de Bento Gonçalves - RS sobre a negritude? Ao disparar a escrita deste tema de dissertação, o ato de um pai-negro é movido pela manifestação de racismo causada na escola, diretamente ao filho Arthur e, com o movimento da pesquisa reivindica, por intermédio da escrita, o lugar de um método de pesquisa como cartógrafo-negro e a sua expressão por meio de desenhos e da escrita da dissertação, que acontece somente com autores negros e negras, o que já ocorre por tal posicionamento político-científico de uma prática de pesquisa pela negritude. Junto ao método, os combates conceituais ocorrem pela racialização do negro, numa perspectiva da negritude. Esse processo tem como objetivo geral de pesquisa cartografar o que dizem as crianças negras matriculadas no segundo ano da alfabetização nas escolas estaduais da cidade de Bento Gonçalves - RS sobre a negritude e, a partir disso, temos os seguintes tópicos investigativos: I. Expressa, através de uma cartografia por meio de desenhos, os operadores de produção de racismo, na perspectiva do cartógrafo-negro; II. Mapeia a presença das crianças negras no primeiro ano da alfabetização, através dos dados de autodeclaração de raça informado pelos responsáveis, nas escolas estaduais, no Município de Bento Gonçalves - RS; III. Elabora o ateliê-negritude, para que as crianças negras que constam no mapeamento do objetivo II expressem suas negritudes; IV. Aponta o que dizem as crianças negras quando participam do ateliê-negritude. Participaram dos ateliês-negritude dez crianças do segundo ano de alfabetização, distribuídas em cinco escolas do município e neste espaço traz o registro que as crianças dizem do racismo, territorializado nos seus cabelos crespos. [resumo fornecido pelo autor]
Keywords: Alfabetização; Crianças negras; Racismo; Negros - Identidade racial; Literacy; Black children; Racism; Blacks - Race identity